One Protestant looks at Centesimus Annus - Armstrong, James (Journal of business ethics, 1993)
“One Protestant Looks At Centesimus Annus” is an attempt to analyze Pope John Paul II's centennial encylical on economic justicein context. It relates the early contributions of Reformation thought to the emergence of laissez-faire capitalism. It describes the “social gospel” as a convergence of the radical implications of 19th century German Protestant scholarship and the harsh economic/social realities of the industrial revolution. Then it compares the economic teachings of the institutional church from Leo XIII and the old Federal Council of Churches to John Paul II and the World Council of Churches one hundred years later. All of this prepares the way for a critical analysis ofCentesimus Annus with a special emphasis on the Pope's understanding of “Christian truth”. Finally there is a postscript relating the encyclical to the ethical challenges facing multinational corporations in developing countries.